The Influence of Market Orientation, Entrepreneurial Orientation, and Innovation on Business Performance (A Study on Garment SMEs in Sukabumi City) - Listiawati, Hana Putri; Komariah, Kokom; Saori, Sopyan (Universitas Muhammadiyah Pontianak, 2025)
This study investigates the impact of market orientation, entrepreneurial orientation, and innovation on the business performance of garment SMEs in Sukabumi City. Employing a quantitative approach with descriptive and associative methods, data were obtained from 38 SME owners through questionnaires. Multiple linear regression analysis was used to assess the relationships between variables. The results indicate that all three independent variables significantly and positively affect business performance. These findings underscore the importance of aligning strategy with market needs and innovation. The study provides valuable insights and practical recommendations for SME entrepreneurs to improve performance and competitiveness through strategic business initiatives.